Humble leadership and its outcomes: A meta-analysis - Luo, Yifei; Zhang, Zeyu; Chen, Qishu; Zhang, Kairui; Wang, Yijiang; Peng, Jianfeng (Frontiers in Psychology, 2022)
The importance of humble leadership has garnered attention from both researchers and practitioners. Unfortunately, despite the accumulation of recent findings on the effects of leader humility, a quantitative review remains scant. In addressing this void, this study is among the first to conduct a meta-analytic review of humble leadership and its outcomes. 84 correlations (N = 16,534) from 53 independent studies are synthesized. The authors found that: (a) humble leadership is positively related to affective commitment (ρ=0.56), affective trust (ρ=0.62), creativity (ρ=0.39), engagement (ρ=0.40), leader-member exchange (LMX) (ρ=0.58), job satisfaction (ρ=0.51), organizational identification (ρ=0.48), psychological empowerment (ρ=0.33), self-efficacy (ρ=0.24), task performance (ρ=0.33), and voice (ρ=0.34); and that (b) humble leadership contributes a significant incremental variance beyond transformational, servant, and ethical leadership in several crucial criterion variables, providing solid evidence for the construct’s uniqueness. However, humble leadership does not explain incremental variance in some criterion variables, indicating that future studies should control for the influence of some positive leadership. We discuss our findings with caution and propose future research directions.